Re-Inventing Teachers’ Competences at Early Childhood Education in Building Characters Needed for Global Competition - Karmila Machmud (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2015)
The goal of this paper is to elaborate and to re-invent the competencies needed by early childhood education teachers. Building children’s character from an early age is significant, but the main problem that is often overlooked is the contribution of Early Childhood Education teachers. Children’s character formation is largely determined by the quality of early childhood teachers. So if we want to instill character values required by our nations, the improvement of the quality of early childhood teachers is very significant. In terms of shaping children’s character, they should be equipped with some important skills and competences, because they have a significant role in building the Indonesian Children’s characters needed in global competition without abandoning their identity as a dignified Indonesian.